2004
DOI: 10.1095/biolreprod.104.029413
|View full text |Cite
|
Sign up to set email alerts
|

Progress with Nonhuman Primate Embryonic Stem Cells1

Abstract: Embryonic stem cells hold potential in the fields of regenerative medicine, developmental biology, tissue regeneration, disease pathogenicity, and drug discovery. Embryonic stem (ES) cell lines are now available in primates, including man, rhesus, and cynomologous monkeys. Monkey ES cells serve as invaluable clinically relevant models for studies that can't be conducted in humans because of practical or ethical limitations, or in rodents because of differences in physiology and anatomy. Here, we review the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 38 publications
2
33
0
1
Order By: Relevance
“…Among them, TRA-1-81 antigen is a keratan sulfate proteoglycan [6,8], which is expressed in undifferentiated cells and dramatically downregulated in differentiated cells. It was suggested that TRA-1-81 and TRA-1-60 may react with the same protein which has sialidase-sensitive epitopes [9].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, TRA-1-81 antigen is a keratan sulfate proteoglycan [6,8], which is expressed in undifferentiated cells and dramatically downregulated in differentiated cells. It was suggested that TRA-1-81 and TRA-1-60 may react with the same protein which has sialidase-sensitive epitopes [9].…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro induction of neural differentiation in ESC also closely mimics molecular mechanisms of embryonic brain development [33]. All these findings make it possible to use rESC as a model for investigating cell lineage relations to better understand primate, including human, embryonic neurogenesis and gliogenesis because the rhesus monkey has the advantage over rodents of being closely related to humans in terms of genetics and physiology [34].…”
Section: Introductionmentioning
confidence: 88%
“…Some feeder-free systems support the culture of undifferentiated hES cells more efficiently than others [8,9], however, porcine and bovine epiblast and ICM cells cultured on a feeder free system did not grow continuously and started senescence or differentiation [10][11][12][13]. In case of the farm animals, ES cell-like cells are also commonly cultured on feeder cells because the molecular pathways and key molecules required in maintaining pluripotency in these species are still unknown [14]. As stated earlier in various reports, homologous feeder cell layers supported self renewal and maintained pluripotent characteristics of human and monkey ES cells, with characteristics similar to those of ES cells cultured on mouse fetal fibroblast (MEF) [9,15].…”
Section: Introductionmentioning
confidence: 99%